STUDI STABILITAS FORMULASI SELF NANO EMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) EKSTRAK DAUN SERUNAI SEBAGAI ANTI DIABETES DENGAN VARIASI KONSENTRASI ASAM OLEAT - Norliani, Rahma; Noval, Noval; Melviani, Melviani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Management of diabetes mellitus can use chemical drugs and traditional medicine. One of the medicinal plants used by the community is chrysanthemum leaves (C.Odorata). The use of traditional medicine still has drawbacks, one of which is that its pharmacological effects are relatively weak and slow, affecting bioavailability and the therapeutic effect is not optimal. The aim of the study was to determine the stability of the formulation of the SNEDDS of chrysanthemum leaf extract as an anti-diabetic agent and to determine the effect of variations in the concentration of oleic acid in the formulation of the SNEDDS on evaluation and stability testing. This research method uses the Quasy Experimental Design method. The simplicia was made into an extract and then made into a nanoemulsion preparation with varying concentrations of oleic acid. The results of this study in the centrifugation test were stable at F3. Unstable hot-cold and freeze-thaw cycle tests. Stable resistance to dilution test at F2 250 ml. Week 0 and 4 accelerated storage tests were stable on F3 and F1. The evaluation results showed that variations in the concentration of oleic acid had no effect on particle size and PDI values ​​but had an effect on the transmittance value (%) as shown in the One Way Anova statistical analysis (p<0.05). The evaluation results showed that F2 with 10% oleic acid concentration was a stable formula because it had the smallest particle size and PDI (Polydispers Index) value.